An intrafamilial phenotypic variability in Ellis‐Van Creveld syndrome due to a novel 27 bps deletion mutation. Issue 10 (26th May 2021) - Zaka, Ayesha; Shahzad, Shaheen; Rao, Hadi Zahid; Kanwal, Sadia; Gul, Asma; Basit, Sulman
Abstract: Ellis‐van Creveld (EvC) syndrome is an autosomal recessive disease, characterized by ectodermal, skeletal, and cardiac anomalies. We report intrafamilial phenotypic variability in three new EvC syndrome cases. Affected males in this study showed only ectodermal abnormalities, whereas an affected female showed the classical presentation of EvC Syndrome, including bilateral postaxial polydactyly of hands and feet, and congenital heart defects. Whole exome sequencing was performed to identify the causative variant, followed by validation and segregation analysis using Sanger sequencing. A homozygous deletion variant (c.731_757del) was identified in exon 6 of the EVC gene (NM_153717.2). The identified variant is considered to be the most likely candidate variant for the EvC syndrome in the family based on previous reports validating the role of EVC variants in the EvC syndrome. The disease correctly segregated in the family members, as all affected members were homozygous, and obligate carriers were heterozygous. Our family is remarkable in highlighting the variable expressivity of the EvC phenotype within the same family, due to a homozygous deletion mutation in the EVC gene. The variable expressivity might be due to the hypomorphic nature of mutation, or the presence of additional variants in modifier genes or in the regulatory regions of the EVC/EVC2 genes.